2012
DOI: 10.1111/j.1447-0756.2012.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective salvage of acute massive uterine bleeding using intrauterine balloon tamponade in a uterine adenomyosis patient on dienogest

Abstract: We present the case of a 37-year-old nulliparous woman in whom acute massive uterine bleeding during dienogest therapy was successfully treated using intrauterine balloon tamponade. Abnormal uterine bleeding and several cases of profuse bleeding causing severe anemia in association with dienogest therapy have been reported, but this is the first reported case involving hypovolemic shock. While successful control of postpartum hemorrhage with intrauterine balloon tamponade has been well described, applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…To summarize, our patient suffered massive genital bleeding originating from severe uterine adenomyosis with leiomyoma. It was previously reported that uterine bleeding might occur with adenomyosis, especially when dienogest was administered, as in the present case . The treatment options for uterine bleeding include pharmacological treatment, angiographic embolization, balloon tamponade, gauze packing, and hysterectomy .…”
Section: Discussionmentioning
confidence: 52%
“…To summarize, our patient suffered massive genital bleeding originating from severe uterine adenomyosis with leiomyoma. It was previously reported that uterine bleeding might occur with adenomyosis, especially when dienogest was administered, as in the present case . The treatment options for uterine bleeding include pharmacological treatment, angiographic embolization, balloon tamponade, gauze packing, and hysterectomy .…”
Section: Discussionmentioning
confidence: 52%
“…Foley catheter insertion was also reported for massive uterine bleeding due to uterine adenomyosis following dienogest . A 9‐Fr Foley catheter was inserted under ultrasonography, and hemostasis was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…A 9‐Fr Foley catheter was inserted under ultrasonography, and hemostasis was achieved. The inflation volume was 3 mL and it was removed the next day . Balloon tamponade can be placed in numerous sites, not only in the uterine cavity for obstetrics, but also in the vagina or endocervix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations